Loggerhead turtle oceanic-neritic habitat shift reveals key foraging areas in the Western Indian Ocean - Monsinjon, Jonathan R.; Laforge, Antoine; Gaspar, Philippe; Barat, Anne; Bousquet, Olivier; Ciccione, Stéphane; Jean, Claire; Ballorain, Katia; Dalleau, Mayeul; Coelho, Rui; Bonhommeau, Sylvain; Bourjea, Jérôme (Frontiers in Marine Science, 2023)
Loggerhead sea turtles (Caretta caretta) use both oceanic and neritic habitats depending on their life stage, eventually undertaking an ontogenetic shift. Juveniles likely start foraging in a purely opportunistic manner and later seek resources more actively. In the Indian Ocean, it is still unclear where oceanic-stage individuals go, what they do, and importantly where they forage. Yet, such information is crucial to protect this endangered species from anthropogenic threats such as bycatch in fisheries. To address this, 67 individuals (66 late juveniles and one adult) bycaught in the open ocean were equipped with satellite tags and released in the Southwestern Indian Ocean between 2008 and 2021. Most individuals traveled to the Northwestern Indian Ocean where they used neritic habitats of the continental shelf (i.e., largely between 0 and 200-m depth). Using hidden Markov models, we identified three types of movements likely associated with traveling, wandering, and foraging behaviors. We found that the movement characteristics of these behaviors differ depending on turtles’ target destination and habitat (oceanic vs neritic), highlighting different strategies of habitat use among individuals of presumably the same life stage (late juveniles). The turtles that traveled to the Northwestern Indian Ocean encountered warmer waters (mean = 27.6°C, min. = 20.6°C, max. = 33.1°C) than their counterparts remaining in the Southern Hemisphere (mean = 22.5°C, min. = 14.6°C, max. = 29.7°C) but were found foraging at locations with comparable biomass of potential prey (mean = 2.5 g C m-2, min. = 0.5 g C m-2, max. = 10.4 g C m-2) once in the Northern Hemisphere. It remains obscure why these individuals undertook a trans-equatorial migration. Once in neritic habitats, the proportion of time spent traveling was considerably reduced (from 33% to 19%) and allocated to foraging instead. In light of this, it is very likely that the individuals migrated to the Northwestern Indian Ocean to undergo an oceanic-to-neritic ontogenetic shift. Our study sheds light on the behavioral ecology of loggerhead turtles and identifies important foraging areas in the Western Indian Ocean, with the top-three most densely used ones being the Gulf of Oman, the Central Somali Coast, and the Western Arabian Sea.